Evaluating Level of Service (LOS) for service coverage in Kuala Lumpur transit system using GIS / Saritha Paramasivam - Saritha, Paramasivam (2013)
Because of heavy traffic and congested roads, it is crucial that most main public transport services in Kuala Lumpur—that is, Putra LRT, STAR LRT, KTM Komuter, KL Monorail, and RapidKL buses—must be continuously improved by the transit agencies to fulfil the commuters’ requirements. Transit planning is essential for transit agencies in all transit systems because commuters rely on these transit systems to travel from one place to another. The quality of service would determine the efficiency and the accessibility of every transit system for a better ridership. Therefore, evaluating the level of service (LOS) for service coverage in the Kuala Lumpur transit system has been determined using a geographic information system (GIS) as a tool for transit planning in this study. The service coverage measures of the quality of service that have been chosen in this study consist of a three-part analysis—namely, service coverage area, transit-supportive area (TSA), and service coverage LOS—for each of the transit system. The detailed census data of the region along the line of services have been collected from the Department of Statistics Malaysia. TSA covered 93% of the area, and only 7% is not a TSA in Kuala Lumpur. The service coverage LOS is calculated with the percentage of TSA served by each transit system. Overall, the percentage of TSAs serving every transit system was less than 60%, and the combination of all transit systems falls below 80%, which is still not efficient for a significant ridership. This study has proven that transit planning is important for transit agencies to provide a superlative quality of service for the commuters.